Self-Healing sebagai Metode Pengendalian Emosi - M. Anis Bachtiar; Aun Falestien Faletehan (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The problems of stress and failure in emotion management among teenagers have always been a major concern among scholars and practitioners. Recent literature has been trying to find the best formula to help teenagers to control their emotions. This study aims to examine the influence of self-healing on teenagers' emotion management. Based on an experimental-quantitative approach including both pre-test and post-test designs, this study details how structured training and practice of self-healing may help individuals in managing their emotions. By taking a research setting in one of the theoretically selected educational institutions, this study periodically tested and observed 40 students as training participants. As a result, apart from demonstrating the uniqueness osf self-healing training which involves spiritual development processes (e.g., pembaiatan, religious learning) and physical exercise (e.g., pencak silat, relaxed breathing training), the findings also show that self-healing has a positive impact on students' ability to control their emotion.